Investigating Relationship between Working Capital Management and Capital Structure - Abdussalam, Abdalla Geth; Mohd Ridzuan, Darun (Global Business Research, 2018)
The main purpose of this paper is to investigate the relationship between working capital management and capital structure quantitatively. Many firms are facing financial deficit issues due to lack of working capital management. Debt policy decisions has been an important tool for the managers to tackle with financial complexities. Quantitative research approach was followed in this paper using self-administered survey questionnaire. Top managers were selected as sample to obtain their views on the WCM components influencing capital structure decisions and the extent to which they felt that these had been considered as successful. The SMART-PLS (Partial Least Square) version 2.0 software was used for the analysis of the results. From the statistical findings it was found that working capital management play an important role in managing capital structure of Malaysian public listed firms. Managers must utilize the budget appropriately and control costs to set performance goals of the organization.